Review of Antimicrobial Resistance in the Environment and Its Relevance to Environmental Regulators - Singer, Andrew C.; Shaw, Helen; Rhodes, Vicki; Hart, Alwyn (Frontiers in Microbiology, 2016)
The environment is increasingly being recognised for the role it might play in the global spread of clinically-relevant antibiotic resistance. Environmental regulators monitor and control many of the pathways responsible for the release of resistance-driving chemicals into the environment (e.g., antimicrobials, metals, biocides). Hence, environmental regulators should be contributing significantly to the development of global and national antimicrobial resistance (AMR) action plans. It is argued that the lack of environment-facing mitigation actions included in existing AMR action plans is likely a function of our poor fundamental understanding of many of the key issues. Here, we aim to present the problem with AMR in the environment through the lens of an environmental regulator, using the Environment Agency (England’s regulator) as an example from which parallels can be drawn globally. The issues that are pertinent to environmental regulators are drawn out to answer: What are the drivers and pathways of AMR? How do these relate to the normal work, powers and duties of environmental regulators? What are the knowledge gaps that hinder the delivery of environmental protection from AMR? We offer several thought experiments for how different mitigation strategies might proceed. We conclude that: 1) AMR Action Plans do not tackle all the potentially relevant pathways and drivers of AMR in the environment; and 2) AMR Action Plans are deficient, in part, because the science to inform policy is lacking and this needs to be addressed.